Early-life nutritional exposures and lifelong health: immediate and long-lasting impacts of probiotics, vitamin D, and breastfeeding. - Berti, Cristiana; Agostoni, Carlo; Davanzo, Riccardo; Hyppönen, Elina; Isolauri, Erika; Meltzer, Helle M; Steegers-Theunissen, Régine P M; Cetin, Irene (Nutr Rev, 2017)
Pregnancy and infancy comprise the most critical stages for conditioning an individual's health, with a number of implications for subsequent risks of morbidity, mortality, and reproductive health. Nutrition may influence both the overall pregnancy outcome and the growth trajectory and immune system of the fetus and infant, with short- and long-term effects on the health of the offspring. Within this context, leading experts at Expo Milano 2015 in Milan, Italy, discussed up-to-date knowledge while providing suggestions and challenges before, during, and after pregnancy. This narrative review summarizes the key issues raised by the experts concerning the interplay between the nutritional environment from conception to early infancy and the offspring's immediate and lifelong health, with a particular focus on epigenetic mechanisms, probiotics, vitamin D, and breastfeeding. Taken together, the findings strengthen the awareness that nutritional exposures occurring from preconception to the postnatal period may be strong determinants of the offspring's health and may provide supportive evidence for current nutritional recommendations and guidelines for pregnant women and infants. Critical topics to be addressed in future research and translated into recommendations of public health relevance are also highlighted.
Keywords: Breast Feeding; Diet; Female; Humans; Infant; Infant Nutritional Physiological Phenomena; Meta-Analysis as Topic; Nutritional Status; Pregnancy; Pregnancy Outcome; Probiotics; Vitamin D

Isolated hypoplasia of abdominal wall muscles associated with fetal ascites. - Travan, Laura; Naviglio, Samuele; Cont, Gabriele; Brovedani, Pierpaolo; Davanzo, Riccardo; Demarini, Sergio (Congenit Anom (Kyoto), 2016)
We report the case of an infant born after parvovirus B19-induced fetal hydrops, who presented at birth with bilateral abdominal wall laxity, which was more evident on the flanks. Imaging exams revealed congenital hypoplasia of oblique abdominal muscles not associated with other anatomical abnormalities except for small liver calcifications. We review the medical literature and identify similar cases associated with fetal ascites. We propose that isolated hypoplasia of abdominal wall muscles can be associated with fetal ascites from various causes, and represents a separate condition from prune belly syndrome.

Time for the 70°C water precautionary option in the home dilution of powdered infant formula. - Silano, Marco; Paganin, Paola; Davanzo, Riccardo (Ital J Pediatr, 2016)
Powdered infant formulas (PIF) are usually not sterile and may frequently be contaminated by several bacteria strains. Among them, Cronobacter species, previously known as Enterobacter sakazakii, is one of the most harmful, since it might be the causative agent of sepsis and meningitis in newborns and preterm infants during the first weeks of life. The mortality rate of these infections is up to 80 %. Therefore, some precautions are required in the home handling and dilution of PIF. Whereas there is wide consensus about the need that a PIF should be used immediately after being diluted or, if not, stored at < "5 °C", still recently the optimal temperature of the water used to dilute PIF is controversial among scientific societies and health agencies. The current knowledge is reviewed in this paper and provides sufficient evidence to cautiously advise the use of hot water at a temperature of "70 °C" in the dilution of PIF in order to prevent the Cronobacter sp. contamination and growth.

Advising Mothers on the Use of Medications during Breastfeeding: A Need for a Positive Attitude. - Davanzo, Riccardo; Bua, Jenny; De Cunto, Angela; Farina, Maria Luisa; De Ponti, Fabrizio; Clavenna, Antonio; Mandrella, Stefania; Sagone, Antonella; Clementi, Maurizio (J Hum Lact, 2015)
The use of medications by the nursing mother is a common reason for interrupting breastfeeding. Few drugs have been demonstrated to be absolutely contraindicated during breastfeeding. Excessive caution may lead health professionals to unnecessarily advise to interrupt breastfeeding, without assessing the latest evidence or considering the risk-benefit ratio of taking a medication versus terminating breastfeeding. To foster an appropriate approach toward the use of medications in breastfeeding women, the Italian Society of Perinatal Medicine created the following policy statement.

An IBCLC in the Maternity Ward of a Mother and Child Hospital: A Pre- and Post-Intervention Study. - Chiurco, Antonella; Montico, Marcella; Brovedani, Pierpaolo; Monasta, Lorenzo; Davanzo, Riccardo (Int J Environ Res Public Health, 2015)
Published evidence on the impact of the integration of International Board Certified Lactation Consultants (IBCLCs) for breastfeeding promotion is growing, but still relatively limited. Our study aims at evaluating the effects of adding an IBCLC for breastfeeding support in a mother and child hospital environment. We conducted a prospective study in the maternity ward of our maternal and child health Institute, recruiting 402 mothers of healthy term newborns soon after birth. The 18-month intervention of the IBCLC (Phase II) was preceded (Phase I) by data collection on breastfeeding rates and factors related to breastfeeding, both at hospital discharge and two weeks later. Data collection was replicated just before the end of the intervention (Phase III). In Phase III, a significantly higher percentage of mothers: (a) received help to breastfeed, and also received correct information on breastfeeding and community support, (b) started breastfeeding within two hours from delivery, (c) reported a good experience with the hospital staff. Moreover, the frequency of sore and/or cracked nipples was significantly lower in Phase III. However, no difference was found in exclusive breastfeeding rates at hospital discharge or at two weeks after birth.

Making the first days of life safer: preventing sudden unexpected postnatal collapse while promoting breastfeeding. - Davanzo, Riccardo; De Cunto, Angela; Paviotti, Giulia; Travan, Laura; Inglese, Stefania; Brovedani, Pierpaolo; Crocetta, Anna; Calligaris, Chiara; Corubolo, Elisa; Dussich, Valentina; Verardi, Giuseppa; Causin, Enrica; et al. (J Hum Lact, 2015)
Early and prolonged skin-to-skin contact (SSC) after birth between a mother and her newborn has been shown to generate beneficial effects on the mother-infant relationship and breastfeeding. Close mother-infant body contact immediately after birth positively enhances exclusive breastfeeding during the hospital stay, with a dose-response relationship. Skin-to-skin contact may ease the infant's transition to extra-uterine life and helps regulate the infant's body temperature and nursing behavior. However, reports of sudden unexpected postnatal collapse (SUPC) soon after birth, in healthy term neonates, in association with SSC, have raised concerns about the safety of this practice. Based on available evidence, we developed a surveillance protocol in the delivery room and postnatal ward of the Institute for Maternal and Child Health of Trieste (Italy). The aim of our protocol is (a) to promote safe mother and infant bonding and (b) to establish successful breastfeeding, without increasing the risk of SUPC. As there is no known effective intervention to prevent SUPC, our protocol has been conceived as a potential best practice.

Position Statement on Breastfeeding from the Italian Pediatric Societies. - Davanzo, Riccardo; Romagnoli, Costantino; Corsello, Giovanni (Ital J Pediatr, 2015)
The 2015 Position Statement on Breastfeeding of The Italian Pediatric Societies (SIP, SIN, SICupp, SIGENP) recognizes breastfeeding as an healthy behaviour with many short and long term benefits for both mother and infant.While protecting, promoting and supporting breastfeeding, neonatologists and pediatricians need specific knowledge, skills and a positive attitude toward breastfeeding. In Maternity Hospitals and in Neonatal Units, appropriate organizative interventions should be applied in order to facilitate the beginning of breastfeeding and the use of mother's/human milk.The Italian Pediatric Societies indicate the desiderable goal of around 6 months exclusive breastfeeding if the infant grows properly according to WHO Growth Charts. In principle, complementary feeding should not be anticipated before 6 months as a nutritional strategy pretending to prevent allergy and/or celiac disease. Eventually, long term breastfeeding should be supported meeting mother's desire.

Breastfeeding and migraine drugs. - Davanzo, Riccardo; Bua, Jenny; Paloni, Giulia; Facchina, Giulia (Eur J Clin Pharmacol, 2014)
PURPOSE: Breastfeeding women may suffer from migraine. While we have many drugs for its treatment and prophylaxis, the majority are poorly studied in breastfeeding women. We conducted a review of the most common anti-migraine drugs (AMDs) and we determined their lactation risk. METHODS: For each AMD, we collected all retrievable data from Hale's Medications and Mother Milk (2012), from the LactMed database (2014) of the National Library of Medicine, and from a MedLine Search of relevant studies published in the last 10 years. RESULTS: According to our review, AMDs safe during breastfeeding are as follows: low-dose acetylsalicylic acid (ASA), ibuprofen, sumatriptan, metoprolol, propranolol, verapamil, amitriptyline, escitalopram, paroxetine, sertraline, acetaminophen, caffeine, and metoclopramide. AMDs compatible with breastfeeding but warranting caution are as follows: diclofenac, ketoprofen, naproxen, most new triptans, topiramate, valproate, venlafaxine, and cyproheptadine. Finally, high-dose ASA, atenolol, nadolol, cinnarizine, flunarizine, ergotamine, methysergide, and pizotifen are contraindicated. CONCLUSIONS: According to our review, the majority of the revised AMDs were assessed to be compatible with breastfeeding.
Keywords: Adrenergic beta-Antagonists; Analgesics, Non-Narcotic; Animals; Anti-Inflammatory Agents, Non-Steroidal; Anticonvulsants; Antidepressive Agents; Breast Feeding; Calcium Channel Blockers; Female; Humans; Migraine Disorders; Tryptamines

Breastfeeding during pregnancy: safety and socioeconomic status. - Monasta, Lorenzo; Cetin, Irene; Davanzo, Riccardo (Breastfeed Med, 2014)
Keywords: Breast Feeding; Female; Humans; Lactation; Male; Pregnancy; Pregnancy Complications; Weaning

From tube to breast: the bridging role of semi-demand breastfeeding. - Davanzo, Riccardo; Strajn, Tamara; Kennedy, Jacqueline; Crocetta, Anna; De Cunto, Angela (J Hum Lact, 2014)
Determination of the optimal timing of breastfeeding initiation for preterm infants is still a challenge for health professionals. Often unjustified delays and restrictions of breastfeeding occur due to non-evidence-based current opinions about preterm infants' feeding capacity. Semi-demand feeding has been proposed for preterm infants during the transition from scheduled to full demand feeding, to promote the establishment of self-regulated oral feeding. Although semi-demand feeding has been shown to be safe and effective in reducing time to reaching oral feeding, the implementation of this feeding pattern for preterm infants in the neonatal intensive care unit (NICU) is still limited. We developed a protocol for the application of semi-demand feeding in preterm infants based on the existing knowledge of preterm infant neurodevelopment and NICU organization and staff experience. The protocol's aim is to attain successful transition from tube feeding to breastfeeding. In this article, we describe the protocol used in the neonatal unit of the Maternal and Child Health Institute of Trieste, a third level care center in northeastern Italy.

Radiological contrast media in the breastfeeding woman: a position paper of the Italian Society of Radiology (SIRM), the Italian Society of Paediatrics (SIP), the Italian Society of Neonatology (SIN) and the Task Force on Breastfeeding, Ministry of Health - Cova, Maria Assunta; Stacul, Fulvio; Quaranta, Roberto; Guastalla, Pierpaolo; Salvatori, Guglielmo; Banderali, Giuseppe; Fonda, Claudio; David, Vincenzo; Gregori, Massimo; Zuppa, Antonio Alberto; Davanzo, Riccardo (Eur Radiol, 2014)
OBJECTIVES: Breastfeeding is a well-recognised investment in the health of the mother-infant dyad. Nevertheless, many professionals still advise breastfeeding mothers to temporarily discontinue breastfeeding after contrast media imaging. Therefore, we performed this review to provide health professionals with basic knowledge and skills for appropriate use of contrast media. METHODS: A joint working group of the Italian Society of Radiology (SIRM), Italian Society of Paediatrics (SIP), Italian Society of Neonatology (SIN) and Task Force on Breastfeeding, Ministry of Health, Italy prepared a review of the relevant medical literature on the safety profile of contrast media for the nursing infant/child. RESULTS: Breastfeeding is safe for the nursing infant of any post-conceptional age after administration of the majority of radiological contrast media to the mother; only gadolinium-based agents considered at high risk of nephrogenic systemic fibrosis (gadopentetate dimeglumine, gadodiamide, gadoversetamide) should be avoided in the breastfeeding woman as a precaution; there is no need to temporarily discontinue breastfeeding or to express and discard breast milk following the administration of contrast media assessed as compatible with breastfeeding. CONCLUSIONS: Breastfeeding women should receive unambiguous professional advice and clear encouragement to continue breastfeeding after imaging with the compatible contrast media. KEY POINTS: • Breastfeeding is a well-known investment in the health of the mother-infant dyad. • Breastfeeding is safe after administration of contrast media to the mother. • There is no need to temporarily discontinue breastfeeding following administration of contrast media.
Keywords: Adult; Breast Feeding; Contrast Media; Female; Humans; Infant; Italy; Neonatology; Practice Guidelines as Topic; Radiology; Societies, Medical

Breastfeeding and neonatal weight loss in healthy term infants. - Davanzo, Riccardo; Cannioto, Zemira; Ronfani, Luca; Monasta, Lorenzo; Demarini, Sergio (J Hum Lact, 2013)
BACKGROUND: Neonatal weight loss is universally recognized, yet poorly understood. Limited professional consensus exists on the definition of lower limit of safe weight loss. OBJECTIVE: Our aim was to assess the extent of neonatal weight loss and its association with selected clinical variables in a population of healthy term infants cared for using a specific protocol on weight loss. METHODS: We retrospectively considered 1003 infants consecutively admitted to the regular nursery of the Institute for Maternal and Child Health "Burlo Garofolo" (Trieste, Italy). We studied the relationship of selected variables with neonatal weight loss recorded during the hospital stay. We also analyzed all readmissions in the first month of life as a result of weight loss and its complications. RESULTS: We observed a mean absolute weight loss of 228 g ± 83g, and a mean percent weight loss of 6.7% ± 2.2%. Weight loss ≥ 10% and > 12% were 6% and 0.3%, respectively. In multivariate logistic regression, cesarean section, hot season, any formula feeding, and jaundice not requiring phototherapy were independently associated with neonatal weight loss ≥ 8%. Conversely, low gestational age status was associated with lower weight loss. Readmission within the first month of life because of dehydration occurred in 0.3% of infants. CONCLUSIONS: Breastfeeding, compared to formula feeding, may not be a risk factor for greater early neonatal weight loss, at least in contexts in which weight is routinely monitored, breastfeeding is repeatedly assessed and appropriately supported, and careful supplementation is prescribed to limit and promptly treat excess weight loss and its related complications.
Keywords: Apgar Score; Breast Feeding; Delivery, Obstetric; Gestational Age; Humans; Infant, Newborn; Length of Stay; Patient Readmission; Retrospective Studies; Seasons; Weight Loss

Breastfeeding at NICU discharge: a multicenter Italian study. - Davanzo, Riccardo; Monasta, Lorenzo; Ronfani, Luca; Brovedani, Pierpaolo; Demarini, Sergio (J Hum Lact, 2013)
BACKGROUND: Human milk is the optimal form of nutrition for infants, especially sick or compromised infants, yet international data suggest that breastfeeding (feeding at the breast) and the use of expressed human milk (mother's and donor's milk) are limited in patients cared for in the neonatal intensive care unit (NICU). OBJECTIVE: The goal of this study was to examine feeding status at hospital discharge among high risk infants. METHODS: We used the 1991 World Health Organization infant feeding definitions, applied to the 72 hour period preceding discharge from the NICU. The study sample consisted of all high risk infants discharged from July 1, 2005, to June 30, 2006 from 13 Italian NICUs. Data on infant feeding in the last 72 hours were collected at discharge from the medical records. RESULTS: We recorded data from 2948 subjects with a median gestational age of 35 weeks (IQR, 32-38), a median birth weight of 2200 g (IQR, 1630-2920) and a median length of stay of 16 days (IQR, 8-33). At discharge, 28% of all infants were fed exclusively with human milk: 31%, 25%, 22% and 33% respectively in the <1500 g, 1500-2000 g, 2000-2499 g and ≥ 2500 g birth weight categories. The proportion of infants not fed with human milk varied from 6 to 82% across different centers. CONCLUSION: Our study found limited breastfeeding and use of human milk among the NICU infants at discharge. At discharge, infants with a birth weight 1500-2499 g were fed exclusively with human milk less than those in higher or lower birth weight categories.
Keywords: Breast Feeding; Humans; Infant, Low Birth Weight; Infant, Newborn; Infant, Premature; Intensive Care Units, Neonatal; Italy; Logistic Models; Multivariate Analysis; Patient Discharge

Human colostrum and breast milk contain high levels of TNF-related apoptosis-inducing ligand (TRAIL). - Davanzo, Riccardo; Zauli, Giorgio; Monasta, Lorenzo; Vecchi Brumatti, Liza; Abate, Maria Valentina; Ventura, Giovanna; Rimondi, Erika; Secchiero, Paola; Demarini, Sergio (J Hum Lact, 2013)
BACKGROUND: TNF-related apoptosis inducing ligand (TRAIL) is a pleiotropic cytokine, which plays a key role in the immune system as well as in controlling the balance of apoptosis and proliferation in various organs and tissues. OBJECTIVE: To investigate the presence and levels of soluble TRAIL in human colostrum and milk. METHODS: The levels of soluble human TRAIL were measured in human colostrum (day 2 after delivery) and breast milk (day 5 after delivery). The presence of TRAIL was also measured in infant formula. RESULTS: Levels of soluble TRAIL in the colostrum and mature human milk were, respectively, at least 400 and 100 fold higher than those detected in human serum. No TRAIL was detected in formula. CONCLUSION: Human soluble TRAIL is present at extremely high levels in human colostrum and human milk and might have a significant role in mediating the anti-cancer activity of human milk.
Keywords: Adult; Apgar Score; Colostrum; Female; Gestational Age; Humans; Infant Formula; Infant, Newborn; Milk, Human; TNF-Related Apoptosis-Inducing Ligand

Does the LATCH score assessed in the first 24 hours after delivery predict non-exclusive breastfeeding at hospital discharge? - Tornese, Gianluca; Ronfani, Luca; Pavan, Carla; Demarini, Sergio; Monasta, Lorenzo; Davanzo, Riccardo (Breastfeed Med, 2012)
AIM: The aims of this study were to analyze the relationship between the LATCH score assessed in the first 24 hours after delivery and non-exclusive breastfeeding at discharge and to identify a cutoff for the LATCH score in order to identify women with higher risk of non-exclusive breastfeeding who may need additional breastfeeding support. SUBJECTS AND METHODS: We conducted a prospective observational study in the Maternity Ward of the Institute for Maternal and Child Health "Burlo Garofolo" (Trieste, Italy) and collected data from 299 mother-infant dyads. RESULTS: The rate of nonexclusive breastfeeding was inversely related to the LATCH score (p<0.001) with non-exclusive breastfeeding infants scoring less (6.9) than infants exclusively breastfed at discharge (7.6) (p=0.001). In multivariate analysis, non-exclusive breastfeeding was also associated with cesarean section, primiparity, and infant phototherapy. In order to support maternity staff in providing targeted interventions, we identified four LATCH score cutoffs associated with as many risk groups for non-exclusive breastfeeding at discharge. CONCLUSIONS: The LATCH score is a useful tool to identify mother-infant pairs who might benefit from additional skilled support in specific subgroups at risk of non-exclusive breastfeeding at discharge. Future research is needed to explore if the LATCH score assessed in the first days of life can also predict the duration of breastfeeding.
Keywords: Adult; Breast Feeding; Female; Health Promotion; Humans; Infant, Newborn; Italy; Logistic Models; Multivariate Analysis; Patient Care Planning; Patient Discharge; Prospective Studies; Risk Assessment; ROC Curve; Sensitivity and Specificity; Social Support

RICH (rapidly involuting congenital hemangioma): not only a definition of wealth. - Abate, Maria Valentina; Davanzo, Riccardo; Bibalo, Chiara; Zennaro, Floriana; Berti, Irene (J Pediatr, 2012)
Keywords: Female; Hemangioma; Humans; Infant, Newborn; Skin Neoplasms

Antidepressant drugs and breastfeeding: a review of the literature. - Davanzo, Riccardo; Copertino, Marco; De Cunto, Angela; Minen, Federico; Amaddeo, Alessandro (Breastfeed Med, 2011)
The use of antidepressants in breastfeeding mothers is controversial: Manufacters often routinely discourage breastfeeding for the nursing mother despite the well-known positive impact that breastfeeding carries on the health of the nursing infant and on his or her family and society. We conducted a systematic review of drugs commonly used in the treatment of postpartum depression. For every single drug two sets of data were provided: (1) selected pharmacokinetic characteristics such as half-life, milk-to-plasma ratio, protein binding, and oral bioavailability and (2) information about lactational risk, according to some authoritative sources of the literature: Drugs in Pregnancy and Lactation edited by Briggs et al. (Lippincott Williams, Philadelphia, 2008), Medications and Mothers' Milk by Hale (Hale Publishing, Amarillo, TX, 2010), and the LactMed database of TOXNET ( www.pubmed.gov ; accessed June 2010). Notwithstanding a certain variability of advice, we found that (1) knowledge of pharmacokinetic characteristics are scarcely useful to assess safety and (2) the majority of antidepressants are not usually contraindicated: (a) Selective serotinin reuptake inhibitors and nortryptiline have a better safety profile during lactation, (b) fluoxetine must be used carefully, (c) the tricyclic doxepine and the atypical nefazodone should better be avoided, and (d) lithium, usually considered as contraindicated, has been recently rehabilitated.
Keywords: Adrenergic Uptake Inhibitors; Antidepressive Agents; Antidepressive Agents, Tricyclic; Biological Availability; Breast Feeding; Depression, Postpartum; Directive Counseling; Drug Monitoring; Female; Humans; Infant, Newborn; Lactation; Lithium Compounds; Maternal Exposure; Milk, Human; Monoamine Oxidase Inhibitors; Pregnancy; Serotonin Uptake Inhibitors

Promoting mother’s milk use in very low birth weight infants: when nutritional hierarchy deals with the professional value system. - Davanzo, Riccardo (J Hum Lact, 2011)
Keywords: Attitude of Health Personnel; Breast Feeding; Health Promotion; Humans; Infant, Newborn; Infant, Very Low Birth Weight; Intensive Care Units, Neonatal

Hot water and preparation of infant formula: how hot does it have to be to be safe? - Davanzo, Riccardo; Giurici, Nagua; Demarini, Sergio (J Pediatr Gastroenterol Nutr, 2010)
Keywords: Guidelines as Topic; Hot Temperature; Humans; Infant; Infant Formula; Water; World Health Organization

Neonatal jaundice and breastfeeding reputation. - Bramuzzo, Matteo; Davanzo, Riccardo (J Hum Lact, 2010)
Keywords: Bottle Feeding; Breast Feeding; Female; Humans; Infant, Newborn; Jaundice, Neonatal; Lactation Disorders; Milk, Human; Risk Factors

Storage of human milk: accepting certain uncertainties. - Davanzo, Riccardo; Travan, Laura; Demarini, Sergio (J Hum Lact, 2010)
Keywords: Food Handling; Humans; Milk, Human; Refrigeration